Three-Dimensional Modeling and Reconstruction of the Crandon Volcanogenic Massive Sulfide Deposit, Northeastern Wisconsin - Lodge, Robert W.D.; Horst, Lucy M. (My University, 2018)
The goal of this research project is to determine the petrogenesis of the stratigraphy hosting the Crandon Cu-Zn volcanogenic massive sulfide (VMS) deposit. Research material (core, documents, etc.), conducted by Exxon Minerals Co. in the 1980s, and was almost completely disposed of by local Native American tribes after they purchased the mineral rights and land containing the deposit in 2003. Any surviving material was either lost or does not exist in a modern context. Using Vulcan 3D mining software, Crandon core samples discovered at the Wisconsin Geologic and Natural History Survey (WGNHS) and the University of Minnesota-Duluth (UMD) have been imported Vulcan software in order to reconstruct the deposit geology. This new model provides spatial context for poorly constrained drill holes and samples and is a guide for future stratigraphic analyses. Geochemical and petrographic analysis of samples from the WGNHS has been computed using x-ray fluorescents (XRF), ICP-MS, and thin section analyses. The preliminary results of these analyses, combined with past research and archived data, will provide a more complete and in-depth understanding of the volcanic and tectonic setting that produced Wisconsin’s only known world-class metal-sulfide deposit. Future work will take advantage of the new 3D model, and compiled digital database to more effectively study the geology and geochemistry of the Crandon deposit
Color poster with text, images, charts, photographs and graphs.
Keywords: Volcanogenic massive sulfide (VMS); Geology; Forest County (Wis.)